Factibilidad para el uso de las normas HACCP en la elaboración de yogurt en el taller de procesos lácteos Espam MFL - Cedeño Cedeño, María Lourdes (2012)
This research was conducted at the Dairy Process Workshops line of yogurt of the ESPAM MFL, descriptive method was used, which contributed with data for the region to determine the technical and feasibility of using HACCP standards in developing yogurt as a strategy in the production of safe food for consumers. The work included three stages: First stage identified the costs of the technical requirements demanded by HACCP standards by conducting comparative tables between the NUTRI-LECHE a company from Cuenca and the ESPAM MFL Workshops, the results achieved in this phase allowed us to determine the type of equipment, infrastructure and signaling in the workshops that require investing. In the second stage, surveys were applied to a sample drawn by the student population of the School of Agribusiness, the results obtained allowed to establish the competitive advantage that has a processing plant working under HACCP standards over other market industries that do not. Third stage produced a budget in which costs are reflected in the implementation of HACCP in workshops and where cash flow is projected to five years considering the income and expenses that would have the Dairy Plant. The execution of this research recommended to the authorities allowed the institution to implement policies in order to reduce risks in consumers’ health.